THE DYNAMIC OF ISLAMIC EDUCATION IN THE DISTRICT OF DAIRI – NORTH SUMATRA PROVINCE - Hadis Purba (State Islamic University of North Sumatra Indonesia, 2019)
The dynamics of Islamic education in the district of Dairi could not be separated from the process of entering and developing Islam in this district. Islamic education developed as many figures carrying Islam established Islamic educational institutions ranging from mosques, Islamic boarding schools and madrasah. This study aims to discover the dynamics of Islamic Education in the district of Dairi. This is descriptive qualitative research where the data are taken from the interview between researcher and correspondents or stakeholder regarding Islamic Education institution and the government. The findings show that the condition of Islamic education in the district of Dairi shows a good development for the advancement of Islamic education in the midst of areas where the majority of the population is non-Muslim. Keywords: District of Dairi, the Dynamic of Islamic Education, Islamic Education Institution.